Analisis Social Media Marketing melalui Instagram: Studi Kasus pada Salah Satu Brand Fashion Wanita Lokal - Alya Hana Pramonoputri; Ryanathan Prabartha; Fikri Akmal Ash Shiddieqy; Nazwa Salsabila Yudithya (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
The purpose of the study is to analyse the social media marketing strategy through Instagram for the   Brand X brand. The research uses a qualitative approach with descriptive techniques, and data is obtained through semi-structured interviews, direct observation, and literature study. The data was analysed inductively to understand the pattern of marketing strategies applied. The results show that   Brand X successfully integrates the five dimensions of Social Media Marketing. The Entertainment dimension is realised through the presentation of interesting and informative content, while Interaction is done by utilising interactive features such as polls, Q&A, and comments to increase audience engagement. The Trendiness dimension is seen from the adaptation of current trends in content visualisation, while Customisation is applied by customising content based on followers' preferences. Finally, the Word of Mouth dimension is encouraged through strategies that motivate audiences to share positive reviews. This strategy is effective in increasing visibility, customer loyalty, and brand relationships with consumers. The research recommends using social media analytics to monitor performance and strengthen future marketing strategies.